ENHANCING EFL LEARNER AUTONOMY THROUGH FLIPPED INSTRUCTION: EFFECTS ON PSYCHOLOGICAL, TECHNICAL, SOCIAL, AND CRITICAL-POLITICAL DIMENSIONS - Yea-Ru Tsai (TEFLIN Journal, 2025)
Despite the fact that existing research has strengthened our understanding of the potential of the flipped classroom (FC) for foreign language development and the advantages it offers for active learning, relatively little research has been conducted on the effect of the flipped model on learner autonomy. This study explored the effects and influencing factors of a flipped model on learner autonomy among English-as-a-foreign language (EFL) learners. The results indicate that students in the flipped group (n = 48) had significantly greater learner autonomy than did their counterparts in the non-flipped group (n = 37) in terms of psychological, technical, social, and cultural-political dimensions. The factor analysis suggests that perceived learner autonomy was highly correlated with environmental factors and individual factors, while a moderate correlation existed between factors related to tasks and learner autonomy. Stepwise regression analyses reveal that environmental factors had the most significant and positive effect on learner autonomy, among which learning resources and teacher response were identified as the most influential variables. These findings confirm that FC is an effective approach for enhancing learner autonomy, with environmental factors playing a crucial role in fostering independent learning.